APPLICATION OF FAST FRAMEWORK IN THE DEVELOPMENT OF UNTAN FMIPA LABORATORY INFORMATION SYSTEM - Arman, Yudha; Sari, Renny Puspita; Mutiah, Nurul; Prawira, Dian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
The laboratory is one of the facilities owned by the FMIPA Laboratory, which is one of the facilities owned by Tanjungpura University to support tridharma activities. There are several problems in laboratory management, namely that management is carried out manually, so it takes a long time to apply for the loan of laboratory equipment and to prepare a free laboratory loan letter. In order to improve services, ensure data security, and accommodate all laboratory data, it is necessary to develop an FMIPA laboratory information system (SILABMIPA). The FAST framework is used in developing SILABMIPA to suit user needs. The analysis and development of SILABMIPA follows the FAST method with the stages Scope Definition, Problem Analysis, Requirements Analysis, Logical Design, Decision Analysis, Physical Design and Integration, Construction and Testing. With the construction of SILABMIPA, it can make it easier for managers to manage laboratories, assist students in applying for and borrowing equipment, as well as making laboratory loan-free certificates. Based on the results of system functional testing against SILABMIPA, it was found that the system operates well in accordance with the user's functional needs, while the results of system interface testing obtained a percentage of 82.60% in the very good category.